A European res publica - Zetterquist, Ola (Oñati Socio-Legal Series, 2011)
The article analyses the fundamental constitutional enigma of the European Union (EU), namely whether the EU can be considered as a (from its Member States) separate and independent constitutional legal order. The EU is often referred to as a legal order sui generis, i.e. of a unique character that defies traditional definitions. More specifically, the notion of an independent and separate EU is at odds with the idea of the sovereign state. The notion of the EU as a legal order sui generis is too much influenced by the models of the sovereign state and sovereignty (in the vein of Thomas Hobbes). The key component in the Hobbesian idea of sovereignty is freedom as non-interference. A sovereign state is consequently a state that is free from, i.e. not interfered with by, external actors like, for example, the EU. Put differently, either the EU is sovereign or the Member States are sovereign. By shifting the perspective to a neo-Roman republican understanding of freedom as non-domination the constitutional picture of the EU will become more nuanced. Res publica is best understood as what citizens hold in common and above their narrow self-interest. According to a republican notion of the constitution the purpose of the law is to eliminate the possibility of arbitrary domination. For that reason, not all interference is to be considered as a restriction of freedom but only those restrictions that cannot be justified according to the res publica. Viewed through the republican prism it can be argued that the EU represents an important advancement in securing freedom as non-domination without implying that the EU must become a state. The fundamental enigma can thus be rephrased as a clash between two diverging concepts of freedom. Whereas the EU will always be at odds with the idea of sovereignty (however framed) it will be much easier to reconcile with the republican ideal.